"Pseudoextinction": Asymmetries in Simultaneous Attentional Selection. - Goodbourn, Patrick T.; Holcombe, Alex O. (Journal of Experimental Psychology. Human Perception & Performance, 2015)
We report robust visual-field asymmetries associated with selecting simultaneous targets. One letter embedded in a rapid serial visual presentation (RSVP) of letters was encircled by a white ring, cueing it as the target to report. In some conditions, 2 RSVP streams were presented concurrently, and targets appeared simultaneously in both. When only 1 stream was cued, performance was similar regardless of whether it was in the left or right visual field. Cueing 2 streams barely affected performance in the left stream, but performance in the right stream suffered markedly. We term this phenomenon pseudoextinction, by analogy to pseudoneglect whereby observers bisect lines to the left of center. Such attentional asymmetries are often believed to originate from a processing imbalance between the 2 cerebral hemispheres. But pseudoextinction also occurred with vertically arrayed streams, with higher efficacy in the superior than in the inferior stream. Mixture modeling of errors indicated that pseudoextinction did not affect the temporal precision or latency of selection episodes; rather, only the efficacy of selection suffered. These findings lead us to suggest that pseudoextinction arises because perceptual traces are activated simultaneously in a visual buffer, but must be tokenized serially. Observers succeed in selecting simultaneous targets because trace activation occurs in parallel. However, observers often fail to report both targets because tokenization proceeds serially: While 1 target is being tokenized, the other's trace may decay below the activation level necessary for tokenization.